Direct current motor control led by microcontroller created PWM - Kunasegeran, Thinesh (2012)
Direct current (DC) motor has already become an important drive configuration for many applications across a wide range of powers and speeds. The ease of control and excellent performance of the DC motors will ensure that it is widely used in many applications. This project is mainly concerned on DC motor speed control system by using microcontroller PIC 16F877A. Pulse Width Modulation (PWM) technique is used where its signal is generated in microcontroller. The program for PWM generation is written in C+ Language using MPLAB IDE software. It is programmed into the microcontroller using PIC Microcontroller Start-up Kit. Then the microcontroller is installed into the motor control circuit. The Microcontroller acts as the motor speed controller in this project. The PWM signal will send to motor driver to vary the voltage supply to motor to acquire desired speed. Besides, it also shows a graph of motor speed versus PWM dutycycle percentage to let the user monitor the performance of the system easily. Based on the result, the readings are quite reliable. Through the project, it can be concluded that microcontroller PIC 16F877A can control motor speed at desired speed efficiently by using Pulse Width Modulation signal.